2021
DOI: 10.1158/1078-0432.ccr-20-3416
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib-Avelumab Combination in Patients with Microsatellite Stable Colorectal Cancer (REGOMUNE): A Single-arm, Open-label, Phase II Trial

Abstract: Purpose: Regorafenib is synergistic with immune checkpoint inhibition in colorectal cancer preclinical models.Patients and Methods: This was a single-arm, multicentric phase II trial. Regorafenib was given 3 weeks on/1 week off, 160 mg every day; avelumab 10 mg/kg i.v. was given every 2 weeks, beginning at cycle 1, day 15 until progression or unacceptable toxicity. The primary endpoint was the confirmed objective response rate under treatment, as per RECIST 1.1. The secondary endpoints included a 1-year nonpro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
48
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 32 publications
12
48
3
Order By: Relevance
“…Although there were no responses, 23 patients presented stable disease (54%), with a median PFS of 3.6 months (95% CI 1.8–5.4), and a median OS of 10.8 months (95% CI 5.9–NA). Increased tumor infiltration by CD8 + T cells at cycle 2 was associated with better outcomes [ 20 ].…”
Section: Immunotherapy-based Combinations In Pmmr/mss Mccrmentioning
confidence: 99%
“…Although there were no responses, 23 patients presented stable disease (54%), with a median PFS of 3.6 months (95% CI 1.8–5.4), and a median OS of 10.8 months (95% CI 5.9–NA). Increased tumor infiltration by CD8 + T cells at cycle 2 was associated with better outcomes [ 20 ].…”
Section: Immunotherapy-based Combinations In Pmmr/mss Mccrmentioning
confidence: 99%
“…High baseline infiltration by TAMs was significantly associated with adverse PFS, whereas increased tumor infiltration by CD8 + T cells from baseline was significantly associated with a better outcome. 107 Inhibition of mitogen/extracellular signal regulated kinase (MEK), a downstream effector of the RAS-MAPK pathway, was found to result in upregulation of PD-L1 and have synergistic effects with the PD-1 inhibitor in preclinical models. 108,109 However, the result of the IMBLAZE370 trial studying the effect of cobimetinib did not meet its primary endpoint of improved OS with atezolizumab plus cobimetinib or atezolizumab versus regorafenib.…”
Section: Icis In Proficient Mmr (Pmmr): Microsatellite-stable (Mss) Mcrcmentioning
confidence: 99%
“…However, they reported that the ORR was 0%, with intolerable toxicities. Unlike the previous two trials that targeted PD-1, an anti-PD-L1 (avelumab) was combined with regorafenib in a phase II REGOMUNE trial [ 96 ]. They reported that the best response was stable disease in 53.5% of patients, whereas there was no objective response in patients with MSS/pMMR mCRC.…”
Section: Overcoming Resistance To Immunotherapy In Mss/pmmr Mcrc With Novel Combination Strategiesmentioning
confidence: 99%